Patent Macracanthorhynchus ingens Infection in a 17-Month-Old Child, Ohio. (23rd December 2020) - Chancey, Rebecca J; Sapp, Sarah G H; Fox, Mark; Bishop, Henry S; Ndubuisi, MacKevin; de Almeida, Marcos; Montgomery, Susan P; Congeni, Blaise
Abstract: Limited data exist on human Macracanthorhynchus infections. We report an asymptomatic 17-month-old who passed eggs and an adult Macracanthorhynchus ingens worm, indicating parasite maturation and reproduction. Macracanthorhynchus ingens may have a greater capacity to mature in humans versus Macracanthorhynchus hirudinaceus.